A Comparative Study of Actuator Configurations for Satellite Attitude Control - Raymond Kristiansen; Olav Egeland; Per Johan Nicklasson (Modeling, Identification and Control, 2005)
In this paper a controllability study of different actuator configurations consisting of magnetic torquers, reaction wheels and a gravity boom is presented. The theoretical analysis is performed with use of controllability gramians, and simulation results with the different configurations are presented and compared regarding settling time and power consumption to substantiate the theoretical analysis. A reference model is also introduced to show how the power consumption can he lowered to the same magnitude as when magnetic torquers are used, without degrading the satellite response significantly.